Nepenthesin activity of three Nepenthes species from Lore Lindu National Park, Central Sulawesi, Indonesia - RAHMADINA RAHMADINA; MHD. RAFI’I MA’ARIF TARIGAN; NURUL HUDA PANGGABEAN; AMRU DAULAY; MUHAMMAD AIZRI FADILLAH; MUHAMMMAD FAISAL; MUHAMMAD IQBAL HIDAYAT; SUSILO SUDARMAN (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Rahmadina, Tarigan MRM, Panggabean NH, Daulay A, Fadillah MA, Faisal M, Hidayat, MI, Sudarman S. 2026. Nepenthesin activity of three Nepenthes species from Lore Lindu National Park, Central Sulawesi, Indonesia. Biodiversitas 27 (2): d270225. https://doi.org/10.13057/biodiv/d270225. Carnivorous pitcher plants of the genus Nepenthes rely on proteolytic enzymes to supplement nutrient uptake in nutrient-poor habitats. Among these enzymes, nepenthesins are acid-stable aspartic proteases found in the digestive fluid. This study compared the morphology and enzymatic activity of three Nepenthes species (Nepenthes maxima, Nepenthes nigra, and Nepenthes tentaculata) from Lore Lindu National Park, Central Sulawesi, Indonesia. Morphological traits were measured in four 10×10 m plots, while nepenthesin activity was tested at four concentrations (50-200 µg/mL) using casein as substrate. Lower pitchers were generally larger and more robust, whereas upper pitchers were slender and showed interspecific variation. Enzymatic activity increased with concentration and ranged from 0.20 to 0.58 U, with N. tentaculata exhibiting the highest proteolytic activity. These results indicate species-specific digestive strategies shaped by habitat conditions and prey availability. Morphological traits showed weak correlations with enzymatic activity, suggesting that biochemical mechanisms play a more decisive role than pitcher structure. Overall, the findings enhance understanding of the adaptive ecology of Nepenthes and suggest the potential relevance of nepenthesins as acid-stable proteases for future biotechnological exploration.